Basiacoung Traditions in Procession Marriage Traditions of the Kuok Kampar Community: Ecotourism - Lisnur Yarahandria; Elida (Postgraduate, University of Mataram, 2023)
This research aims to describe the implementation process, meaning, and function of Basiacoung in the traditional Kuok Kampar wedding party procession. This type of research is qualitative research. Data collection techniques in this research were triangulation, interviews, observation, documentation, and literature study, while data analysis was inductive. Based on data analysis, it can be concluded that the structure, semiotic meaning, function, and values of Basiacoung in the marriage procession of the Kampar community can be identified as several important aspects. The traditional marriage procession of the Kampar community consists of the first several stages of maantau tando, Maantau tando is the initial stage of the intention to carry out the marriage contract, where the man visits the prospective bride's house. Second, pick up the groom, who is sent by the ninik mamak (the groom). Picking up the groom will be sent by the groom's ninik mamak involving clever experts from the bride's tribe, Anak mamak (bako party) of the bride or bako who is the nephew of the bride's father and Simondo people, Third Ulu bajawek, Implementation of ulu bajawek Usually it will be accompanied by a pat, where the pat is a symbol of the greatness of the ninik mamak which symbolizes that it is the handover of the groom who has been picked up by the bride at the previous time.